1989
DOI: 10.1002/j.1537-2197.1989.tb11304.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Post‐translational Modification of Triose Phosphate Isomerase (Tpi) in Isoëtes (Isoëtaceae)

Abstract: As part of an electrophoretic study on Isoëtes, a number of Neotropical and North American species were examined for allozyme variation in TPI. Three of these species—I. storkii, I. flaccida, and I. mexicana—exhibit three distinct zones of TPI activity. The two most anodally migrating zones are comparable to the two zones found in most angiosperms and in several other species of Isoëtes. The single or three‐banded phenotypes produced at these loci correspond, respectively, to the homozygous and heterozygous pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The dimeric condition is typical ofvascular plants (Gottlieb 1981). However, a similar "monomeric" TPI locus has been recently reported in Isoetes (Hickey, Guttman, and Eshbaugh 1989) and evidently results from a post-translational modification of the TPI enzyme. Activity for Tpi-1 was not observed in the absence of the substrate dihydroxyacetone phosphate, indicating that it was not a nonspecific protein.…”
Section: Locisupporting
confidence: 72%
“…The dimeric condition is typical ofvascular plants (Gottlieb 1981). However, a similar "monomeric" TPI locus has been recently reported in Isoetes (Hickey, Guttman, and Eshbaugh 1989) and evidently results from a post-translational modification of the TPI enzyme. Activity for Tpi-1 was not observed in the absence of the substrate dihydroxyacetone phosphate, indicating that it was not a nonspecific protein.…”
Section: Locisupporting
confidence: 72%
“…Our results showed that additives such as sodium metabisulfite and ascorbic acid, which are important to reverse or prevent the oxidative formation of quinones (Loomis, 1974), were needed to solubilize and maintain a higher number of esterase isozymes. Metabisulfite can form a stable covalent complex with phenols that does not react with PVP-40 (Arulsebar et al, 1986;Buckley et al, 1988); ascorbic acid will reduce quinones (Loomis, 1969), not reducible by β-mercaptoethanol (Shaw et al, 1987;Buckley et al, 1988;Hickey et al, 1989;Krebs and Hancock, 1989;Laguidah and Hanna, 1989). Thus, the extraction solution for esterase analysis in young leaves of M. esculenta required two phenolcomplexing agent and four antioxidant agents.…”
Section: Discussionmentioning
confidence: 99%
“…TPI in Cystopteris is composed of two comigrating isozymes, TPI1 and TPI2, that apparently are sequestered in different cellular compartments and thus do not interact (Haufler et al 1990). TPI1 is a typical dimeric protein and TPI2 has been interpreted as a dimeric protein with post-translational modification (Gastony 1988;Hickey et al 1989;Kephart 1990 We inferred that the three distinct, multilocus band patterns observed in PGI2 and TPI correspond to C. fragilis, C. tenuis, and C. fragilis…”
Section: Isozymes the Putative Loci Pgi-2 And Tpimentioning
confidence: 95%
“…Two allozymes, denoted a and b, were observed at both TPI1 and TPI2. TPI2 shows a sixbanded pattern attributed to post-translational modification(Gastony 1988;Hickey et al 1989). For TPI2, "mp," a letter, and a number correspond to "modified individuals taken from three widely separated populations; in each case the sporophytes had aborted spores.…”
mentioning
confidence: 99%